ANALISIS KORELASI ANTARA KEBIASAAN BELAJAR DENGAN HASIL BELAJAR MAHASISWA PADA MATA KULIAH KOMPUTER JARINGAN DI FAKULTAS ILMMU KOMPUTER UNIVERSITAS SAINTEK MUHAMMADIYAH - Dora Bernadisman; Rendy Yudha Wisudya; Nasirudin; Siti Tatimah; Lisa Arliana (LPPM Universitas Cipta Mandiri, 2024)
This research aims to find out whether there is a correlation between study habits and student learning outcomes in computer network courses at the Faculty of Computer Science. This type of research uses quantitative research with correlational analysis techniques. The population in this study was 204 students and the sample used was 30 students from the Faculty of Computer Science. The data collection techniques used were observation, documentation and questionnaires which were analyzed using descriptive statistics. Instrument prerequisite tests include validity tests and reliability tests. Analysis prerequisite tests include normality tests. Hypothesis testing includes product moment correlation tests and significance tests. Based on the results of data analysis calculations, the rcount value of 0.5526 is greater than the rtable value of 0.3610 with a significance level of 5% and is in the medium category. Thus, it can be concluded that there is a positive correlation between study habits and learning outcomes for students at the Faculty of Computer Science.